KLASTERISASI SENTIMEN ULASAN PENGGUNA APLIKASI BCA MOBILE PADA PLATFORM GOOGLE PLAY STORE DENGAN ALGORITMA K-MEANS CLUSTERING - Gilbert Sanko Sunarko; Wasino; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Financial banking app is increasingly becomes part of daily lifestyle. From survey conducted by Top Brand Index showed one of the most popular banking app is BCA Mobile. This study was conducted to analyze BCA Mobile app user feedback from App reviews in google play store platform. The data is collected using scrapping method with google-play-scrapper library in python. Using K-Means Clustering algorithm to analyze 662 reviews in 26 December 2022 until 30 December 2022 time period. The clustering process is supported by Term Frequency-Inverse Document Frequency weighting method to help calculate the importance of a word in a set of document. This clustering process produces ten cluster, with silhouette score of 0.1027277 and average star rating of 2.65.